2013
DOI: 10.1142/s1363919613500126
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling From Standards — Process Management and Technical Innovation in Software Development Organisations

Abstract: The paper explores process management standards in software development organisations. It centres on the question how organisations manage the compliance with process standards as well as the need for ongoing technical innovation at the same time. It refers to former studies where it was concluded that process management standards tend to crowd out technical innovations in organisations. By reconsidering the coupling approach of Orton and Weick (1990) we show based on four case studies that it does not apply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Designers of MCS suppose a certain impact of the MCS on behavior in its context of use (Fried 2010;Fried et al 2013). However, Cat1 studies hardly take into consideration that the design and the actual use of MCS in the context of innovation differ and assume that a MCS constantly produces the same output.…”
Section: Categorization 1: Types Of Managerial Control In the Contextmentioning
confidence: 99%
“…Designers of MCS suppose a certain impact of the MCS on behavior in its context of use (Fried 2010;Fried et al 2013). However, Cat1 studies hardly take into consideration that the design and the actual use of MCS in the context of innovation differ and assume that a MCS constantly produces the same output.…”
Section: Categorization 1: Types Of Managerial Control In the Contextmentioning
confidence: 99%
“…Tjosvold, Andrews and Struthers [30] demonstrated that coercive power influence by managers does not always lead to a team's full acceptance of the decision in question. In fact, evidence shows that teams tend to resist what they consider as standardized (or institutional) solutions enforced by the top when in disregard of the conditions on the ground [39,40]. Team members, based on their professional experiences from everyday work, consider themselves competent enough to judge the best course of action and therefore often show "cynical resistance" or, as expressed in terms of Social Interdependence Theory, "bungling".…”
Section: Power Influencementioning
confidence: 99%
“…We believe that the way organizations meta-structure multiple process standards has an enormous influence e.g. on the innovating activities of an organization (Fried, 2010;Fried et al, 2013).…”
Section: Andrea Fried Linköping University Swedenmentioning
confidence: 99%